Estoppel In Boustead’s Case: A Move Away From Reliance Towards Unconscionability - Cheong, May Fong (Journal of Malaysian and Comparative Law, 1999)
The Federal Court’s decision in Boustead Trading (1985) Sdn Bhd v Arab-Malaysian Merchant Bank Bhd (hereafter referred to as "Boustead’s case") has signified a new era for the doctrine of estoppel in Malaysia.